Modeling Decisions for Artificial Intelligence 5th International Conference, MDAI 2008, Sabadell, Spain, October 30-31, 2008, Proceedings - Narukawa, Yasuo (Lecture Notes in Artificial Intelligence, 2008)
This book constitutes the refereed proceedings of the 5th International Conference on Modeling Decisions for Artificial Intelligence, MDAI 2008, held in Sabadell, Spain, in October 2008. The 19 revised full papers presented together with 2 invited lectures were thoroughly reviewed and selected from 43 submissions; they are devoted to theory and tools for modeling decisions, as well as applications that encompass decision making processes and information fusion techniques. The papers are organized in topical sections on aggregation operators, decision making, clustering and similarity, computational intelligence and optimization, as well as data privacy.